Circulating SCCA–IgM complex is a useful biomarker to predict the outcome of therapy in hepatocellular carcinoma patients. (18th August 2017) - Guarino, Maria; Di Costanzo, Giovan G.; Gallotta, Andrea; Tortora, Raffaella; Paneghetti, Laura; Auriemma, Francesco; Tuccillo, Concetta; Fassina, Giorgio; Caporaso, Nicola; Morisco, Filomena
Abstract: Introduction: Hepatocellular carcinoma (HCC) develops in about 3–4% of cirrhotic patients every year. The squamous cell carcinoma antigen (SCCA) has been found elevated in liver cancer specimens by immunohistochemistry, and detected in complex with IgM (SCCA-IgM) in the serum of patients with HCC. The aim of this study was to evaluate the ability of serological SCCA-IgM levels to predict the efficacy of HCC therapy. Materials and methods: From April 2012 to April 2014, 131 patients with a new diagnosis of HCC were enrolled. The HCC diagnosis was made according to the EASL guidelines. The patients were staged and treated according to the BCLC Staging System: BCLC stages A and B were treated with locoregional therapy, and BCLC stage C was treated with Sorafenib. Response to therapy was evaluated according to the mRECIST criteria. Serum SCCA-IgM levels were determined by a commercially available ELISA kit at basal time ( T 0 ) and after one month of treatment ( T 1 ). Results: At baseline and one month into therapy, SCCA-IgM levels were significantly lower ( p value <.05) in patients who responded to therapy compared to those who did not respond (median SCCA-IgM level [25th + 75th percentile] at T 0 :115.1 AU/mL [50.0 + 174.4] vs. 149.1 AU/mL [111.3 + 198.8]; median SCCA-IgM level [25th + 75th percentile] at T 1 : 113.4 AU/mL [50.0 + 194.2] vs. 170.6 AU/mL [111.7 + 344.2]). Conclusion: Our study suggests that the SCCA-IgM determination could be helpful in predicting the response to therapy in patients with HCC.